KEEFEKTIFAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA POP-UP BOOK RANTAI MAKANAN TERHADAP HASIL BELAJAR IPAS KELAS IV SD NEGERI KARANGTEMPEL - Vionela Ulfatun Nisyak; Arfilia Wijayanti; Fillia Prima Atharina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model assisted by pop-up book media on students' learning outcomes in science and social studies (IPAS) on food chain material in fourth grade of SD Negeri Karangtempel. This research used a quantitative approach with a pre-experimental design of one-group pretest-posttest. The subjects were 20 students. Data were collected through tests, observations, and documentation. The data were analyzed using normality test, paired sample t-test, and N-Gain. The results showed that the data were normally distributed and there was a significant difference between pretest and posttest scores (Sig. 0.000 < 0.05). The N-Gain score was 0.5433 (moderate category). In addition, students' affective and psychomotor aspects improved into good and very good categories. Therefore, it can be concluded that the PBL model assisted by pop-up book media is effective in improving students' learning outcomes.